ЖАҢА ҚЫТАЙ ӘДЕБИЕТІНІҢ ҮЗДІК ЖАЗУШЫСЫ МАУ ДҮН. - Сейдахмет, Э. (Journal of Oriental Studies, 2016)
В статье рассматривается творчество и биографиявыдющегося писателя новой китайскоq литературыМао Дуня.The article deals with the creative activity andbiography of Mao Dun an outstanding writer of modernChinese literature.